A comparison of the prevalence of anti-Liver/Kidney Microsome antibody type-1(LKM-1) in individuals with chronic hepatitis C and those with autoimmune hepatitis - AL- Obeidy, Eman Sh.; Abbs, Nahida R.; AL-Derzi, Aida R. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Autoantibodies are frequently found in patients with chronic hepatitis C, which suggests that HCV elicit an immune response in the host. ). The relationship of type-2 AIH to chronic hepatitis C (HCV) is an interesting and as yet unresolved problem. Importantly, antibodies to liver/kidney microsome type-1 (LKM1), the serologic marker of type 2-AIH, have been recognized in serum of some patients with chronic hepatitis C. Methods: Anti-liver kidney microsome type 1 (LKM-1) autoantibodies were studied by indirect immuno florescence assay (IIF) and confirmed by immunoblot in the serum of 73 Iraqi patients with autoimmune hepatitis (AIH) in comparison with 50 patients control (HCV infection) and 50 healthy individuals. Results: anti-LKM 1 with high titers (≥1/160) present in serum of all patients with AIH-2, whereas they present in titer (≤1/80) in serum of 19 patients with chronic HCV, while all healthy control group are negative. Conclusion: AIH is easily distinguished from chronic viral hepatitis since patients with AIH are more commonly women than those with chronic viral hepatitis, and they have higher serum levels of aspartate aminotransferase, bilirubin, gamma-globulin, IgG, alkaline phosphates, and higher frequency of multilobular necrosis on histologic examination than counters with chronic viral hepatitis.